2017
DOI: 10.1117/1.oe.57.1.011014
|View full text |Cite
|
Sign up to set email alerts
|

Multiheterodyne spectroscopy using interband cascade lasers

Abstract: Abstract. While midinfrared radiation can be used to identify and quantify numerous chemical species, contemporary broadband midinfrared spectroscopic systems are often hindered by large footprints, moving parts, and high power consumption. In this work, we demonstrate multiheterodyne spectroscopy (MHS) using interband cascade lasers, which combines broadband spectral coverage with high spectral resolution and energy-efficient operation. The lasers generate up to 30 mW of continuous-wave optical power while co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…It has to be emphasized that the proposed hybrid locking only locks the RF spectrum, and the optical spectrum partially drifts due to an unlocked offset frequency. In this point of view, the dual-comb system with the hybrid locking method stands between the computationally corrected dual-comb system 26 and the one that is fully referenced to an optically rectified comb. 8 ■ METHODS THz QCL.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has to be emphasized that the proposed hybrid locking only locks the RF spectrum, and the optical spectrum partially drifts due to an unlocked offset frequency. In this point of view, the dual-comb system with the hybrid locking method stands between the computationally corrected dual-comb system 26 and the one that is fully referenced to an optically rectified comb. 8 ■ METHODS THz QCL.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Digital approaches that employ digital mixing, filtering, frequency shifting, etc. analogous to hardware implementations were also applied to various systems for obtaining stable dual-comb signals: THz and mid-infrared QCL frequency combs, interband cascade laser frequency combs, mid-infrared silicon microresonators, and near-infrared waveguide mode-locked lasers. We also demonstrated that instead of locking four different frequencies of a dual-comb laser system, we can stabilize the dual-comb signal as a whole. For example, by phase locking one of the dual-comb line to a RF synthesizer, all dual-comb lines are much more stabilized .…”
Section: Introductionmentioning
confidence: 97%
“…The special section papers addressed holographic wavefront printing for 3-D display, 1 real-time reconstruction for holographic 3-D displays, 2 computational photon-counting light detection and ranging (LiDAR) sensor for 3-D imaging, 3 aspheric lens mounting to achieve fine decentration and tilt accuracy, 4 and multi-heterodyne spectroscopy with interband cascade lasers for chemical sensing. 5 The top downloaded paper provided a tutorial on the characterization of Moiré effects that arise in displays, 6 and the two review papers provided state-of-the-art assessments of self-mixing interferometry for mechanical engineering applications, 7 and high-fidelity imaging spectrometer design for airborne and space-based remote sensing. 8 The two regular papers in the top-ten list included a theoretical paper describing a momentum exchange theory for photon diffraction that uses momentum transfer probability distributions as an alternative to classical wave theory, 9 and an applied paper on an underwater laser communications system based on a 680 nm vertical external cavity surface emitting (VECSEL) laser to achieve wider bandwidth than more prevalent blue-green laser systems.…”
Section: Year In Reviewmentioning
confidence: 99%
“…In many implementations, DCS employs OFC generated using mode-locked lasers 21 , but electro-optical OFC techniques offer a modular solution with configurable resolution and spectral range 22 , 23 . Electro-optic DCS uses a single optical seed to generate both OFCs, which translates into an intrinsic synchronization between the pair of OFCs, hence providing enhanced phase and amplitude stability 24 . Although DCS systems have demonstrated their remarkable capabilities from the visible to the MIR and THz windows in several fields such as metrology, vibrational spectroscopy, or ranging 21 , there is no current demonstration of their usefulness when it comes to dispersive or turbid media, which is the area in which NIRS excels, since scattering seriously damages the coherence needed between the OFC arms of DCS systems.…”
Section: Introductionmentioning
confidence: 99%